2020
DOI: 10.1111/acel.13128
|View full text |Cite
|
Sign up to set email alerts
|

miR‐155‐5p inhibition rejuvenates aged mesenchymal stem cells and enhances cardioprotection following infarction

Abstract: Aging impairs the functions of human mesenchymal stem cells (MSCs), thereby severely reducing their beneficial effects on myocardial infarction (MI). MicroRNAs (miRNAs) play crucial roles in regulating the senescence of MSCs; however, the underlying mechanisms remain unclear. Here, we investigated the significance of miR-155-5p in regulating MSC senescence and whether inhibition of miR-155-5p could rejuvenate aged MSCs (AMSCs) to enhance their therapeutic efficacy for MI. Young MSCs (YMSCs) and AMSCs were isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 39 publications
0
54
0
Order By: Relevance
“…Mfn1 silencing abrogates the protective effect of miR-181c on BMSCs under oxidative stress conditions (Fan et al, 2019). Inhibiting miR-155-5p or Mfn2-siRNA reverses mitochondrial hyperfusion-mediated senescence in MSCs, and transplantation of aged MSCs pretreated with anti-miR-155-5p significantly ameliorates cardiac dysfunction in an infarction mouse model (Hong et al, 2020). miR-214 improves fibroblast differentiation of ASCs by directly binding to the Mfn2 3 -UTR, enhancing ASC-mediated repair in pelvic floor dysfunction in rats with birth trauma.…”
Section: Msc-based Mitochondrial Therapeuticsmentioning
confidence: 99%
“…Mfn1 silencing abrogates the protective effect of miR-181c on BMSCs under oxidative stress conditions (Fan et al, 2019). Inhibiting miR-155-5p or Mfn2-siRNA reverses mitochondrial hyperfusion-mediated senescence in MSCs, and transplantation of aged MSCs pretreated with anti-miR-155-5p significantly ameliorates cardiac dysfunction in an infarction mouse model (Hong et al, 2020). miR-214 improves fibroblast differentiation of ASCs by directly binding to the Mfn2 3 -UTR, enhancing ASC-mediated repair in pelvic floor dysfunction in rats with birth trauma.…”
Section: Msc-based Mitochondrial Therapeuticsmentioning
confidence: 99%
“…These studies include both preclinical and clinical trials of either autologous or allogeneic MSCs. Infusion of MSCs has been performed to evaluate their safety and therapeutic efficacy in diseases of the immune[ 3 ], hematological[ 4 ], cardiovascular[ 5 , 6 ], nervous[ 7 , 8 ], respiratory[ 9 ], digestive[ 10 ], skeletal[ 11 ], endocrine[ 12 ], and reproductive[ 13 ] systems[ 14 ]. To date, more than 1000 MSC-based clinical trials have been registered in the United States National Institute of Health database[ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CAB39, a component of the trimeric LKB1-STRAD-CAB39 complex, contributes to the stabilization of LKB1 to STRAD binding and is recognized as an upstream activator of AMPK due to its role in activating AMPK signaling by phosphorylating AMPK α 1 on residue Thr-172 [ 42 ]. It has been reported that CAB39 is associated with MSC senescence, which occurs in an AMPK-dependent manner [ 43 ]. In the current study, our results showed a decrease in the expression of CAB39 and p-AMPK and an increase in the expression of p-mTOR in aging DPSCs when compared to young DPSCs.…”
Section: Discussionmentioning
confidence: 99%